The Relationship Between of Psychological Capital and School Counsellors Burnout : A Systematic Literature Review - Aniyatussaidah Aniyatussaidah; Herdi Herdi (Universitas Pendidikan Mandalika, 2023)
This research aims to describe the relationship between psychological capital and school counsellors’ burnout. This research method employed a Systematic Literatur Review, collected reading material from various scientific articles (SCOPUS, EBSCO and SINTA) and subsequently compared relevant theories and research results. Based on the results of a literature study conducted, it was found that there was a significant relationship between psychological capital and school counsellors' burnout. A high state of psychological capital (hope, belief, resilience, and optimism) can provide energy for school counsellors to control behavior and reduce symptoms of burnout (fatigue, negative work environment, indifference to clients, feeling incompetent as a school counselor, and chaotic personal life). School Counsellors who have hope will have goals and know the way to achieve these goals. It makes the school counsellors able to overcome things that make theme burnout. School Counsellors will become more resilient, confident, and optimistic in carrying out their role as school counsellors.